Respuesta :

Answer:

Step-by-step explanation:

Factorize the expression.

Sum = 7

Product = 12

Factors = 4 , 3

4 + 3= 7 & 4*3 = 12

x² + 7x + 12 = x² + 4x + 3x + 4*3

                 = x(x + 4) + 3(x + 4)

                 = (x + 4)(x + 3)

Sum = -1

Product = -12

Factors = (-4) , 3

(-4) + 3 = (-1)   & (-4)*3 = -12

x² - x - 12 = x² - 4x + 3x - 4*3

               = x(x - 4) +3(x - 4)

               = (x -4)(x +3)

[tex]\sf \dfrac{x^{2}+7x+12}{x^{2}-x-12}=\dfrac{(x+4)(x + 3)}{(x -4 )(x + 3)}\\\\\bf \text{(x +3) in the numerator and denominator will get cancelled}[/tex]

                   [tex]=\dfrac{x+4}{x-4}[/tex]

Answer:

B

Step-by-step explanation: